2014
DOI: 10.1002/art.38281
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Does Medication Use or Disease Activity During Pregnancy in Patients With Rheumatoid Arthritis Affect Bone Density in Their Prepubertal Offspring?

Abstract: Objective. Prednisone use and active disease are associated with reduced bone mineral density (BMD) in patients with rheumatoid arthritis (RA). Either or both of these factors may be inevitable during pregnancy in women with RA, but it is unknown whether they variables influence the BMD of the offspring. This study was undertaken to investigate whether medication use or disease activity during pregnancy in RA patients influences the BMD of their prepubertal offspring.Methods. Mothers (n ‫؍‬ 255) participated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In our study, we did not explore the effect of antenatal prednisone exposure on the BMD of the offspring. However, in a previous study by de Steenwinkel et al ,55 they investigated the influence of medication use and disease activity of the mother during pregnancy on the offspring at the age of approximately 7 years. In that study, a dual x-ray absorptiometry scan was performed in 108 children born to women with RA.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we did not explore the effect of antenatal prednisone exposure on the BMD of the offspring. However, in a previous study by de Steenwinkel et al ,55 they investigated the influence of medication use and disease activity of the mother during pregnancy on the offspring at the age of approximately 7 years. In that study, a dual x-ray absorptiometry scan was performed in 108 children born to women with RA.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by better disease activity control although this was not reflected by the ESR or the DAS-28 ESR. Although a study of children whose mothers were treated with sulphasalazine had higher total body bone mineral density (BMD) [23], other studies have not shown any association between MTX either alone or in combination with other DMARDs and incident fractures or BMD [24]. We postulate that this may be because disease activity measures were taken at one point in time rather than an average value over time.…”
Section: Discussionmentioning
confidence: 94%
“…We were surprised at the absence of studies that examined a range of other factors that could potentially influence offspring bone health in a life course perspective. Among the factors that have not been adequately addressed, except for in animal models, are prenatal exposure to, e.g., infections (e.g., cystitis); prolonged pregnancy; hyperemesis gravidarum; maternal use of medication during pregnancy, i.e., corticosteroid [43][44][45][46] or selective serotonin reuptake inhibitors [47]; endocrine disruptive chemicals [48][49][50][51]; and estradiol concentrations [52,53]. Moreover, we did not detect any studies that examined the influence of either insulin resistance during pregnancy or gestational diabetes on bone health among adult offspring.…”
Section: Directions For Future Researchmentioning
confidence: 99%